Pesalai passion play in mannar - Samarakoon, K. (University of Jaffna, 2012)
The passion play in Pesalai is unique to Sri Lanka as it is probably the only passion play in the world that is entirely acted using life sized puppets. The play is based on the script ‘Viyakula Pirisangam’ which is the Tamil version of Father Jacolme Gonsalves Sinhala script of ‘dukkapraptha natya saha deshana navaye pasan potha’. The Pesalai passion play has a history of performance of over 200 years. The year 1983 was when all nine acts were performed before the ethnic unrest in the country. Since the Pesalai church and the Fatima Madya Maha Vidyalaya provided shelter to hundreds of refugees till almost 2008 they had no provision to stage the passion play again till 2000. At this point the cast had to build a replica of the original stage its original been erected in 1907 at the Pesalai church, at the playground of the Fatima Madya Maha Vidyalaya to perform a few of the acts. Since then the passion play has been performed in 2003 and then in its original ‘stage’ at the church in 2008, 2010 and 2012. The passion play of the pre-war era was performed on stage by the actors while the readings and chants were narrated off stage. Since 2000, under the direction of Kalabhushana S.A. Miranda there are hymns and pasams been sung to accompaniment on keyboard music. Also a notable change is that there is now dialogue between the characters and not a narration. The costumes too have undergone changes in the post war performances. The aim of this study is to trace the roots of the music of the Pesalai passion play and its influences on the other passion plays within Sri Lanka as this was the root and first passion play acted in Sri Lanka from over 400 years ago. Another point of interest that would be investigated is the changes made for the performance in troubled years of the past years. Video and Audio recordings will be made with a main focus to determine the roots of the music of the play. This is important to my study as the music of the Pesalai passion play is authentic and remains without a considerable change to date. Moreover, structured and unstructured interviews will be used to gather in-depth information from a variety of persons knowledgeable and involved in the Pesalai passion play. This research will explore two main questions with regard to the evolution of passion play music in Sri Lanka. The questions posed are (i) the relation to the cultures and music traditions that have influenced the music of Pesalai passion play and (ii) what are the music traditions that are imbibed in the Pesalai Passion Play music? The hypothesis of this study is that the Pesalai passion play has not undergone a metamotphosis of change at many levels: Concentrating on the music, this study states that the music is authentic and directly influenced by the Karnatic idiom. One of its main influences is also being Konkani Music from Goa.